Conjeturas sobre Walsh a cuarenta años de la «Carta abierta de un escritor a la Junta militar» - Kaufman, Alejandro (Facultad de Periodismo y Comunicación Social, 2017)
The author goes through the conditions of extermination that occurred in Argentina in the 1970s and focuses on problems related to horror, consent, denunciation and memory. In this line, he maintains that the interlocutors of «Carta abierta de un escritor a la Junta Militar» (1977) are not the perpetrators of extermination: it is an interpellation to the consent determined by the silence before the censorship. Finally, points out that a current reading of the Charter allows understanding how was weaving the warp that structured the Argentine collective experience of memory and human rights in its links intimate with the revolutionary saga in its abysmal fall into extermination.